Survey and Distribution of Fern - Allies and Ferns of Chakrata Forest Division, Uttar Pradesh - Kumar, Santosh; Raizada, M. B. (Indian Forester, 1989)
An account of the Pteridophytes occurring in Chakrata, of Dehra Dun District, has been given. An enumeration comprising 10 species of Fern-allies in 4 genera and 4 families and 93 species of Ferns belonging to 41 genera and 19 families are given.